PROBLEMS ON IMPLEMENTING THE POLITENESS PRINCIPLE IN TEACHING AND LEARNING SPEAKING - Widyasari, Fibriani Endah (IKIP PGRI MADIUN, 2016)
This study is conducted to investigate the case appears in teaching and learning speakingÂ regarding to problems on implementing the politeness principle faced by students. Recently, phenomenon happen among students in conversation that fail to provide appropriate politenessespecially toward elders can be illustrated as the basic assumptions from the way they use utterances and their failure on paying attention of social class, age, sex when they communicate to others. This phenomenon brings questions that become the bases of the aims of this study to find outproblem appears on implementing politeness principle in teaching and learning speaking, to find out factors cause the problems appear, and formulate suitable recommendations to provoke students using appropriate utterances and maxim in order to make good relationships and distinguish context toward different age, sex and status of conversation participants who they interact with. This study belongs to the case study research and the data collected from observations and interviews. The findings show that the problems often made by students are they utter wrong expressions for certain situations, they do not greet, thank and ask for sorry to anyone they involved with included the elders. The problems that faced by students in implementing politeness principal in speaking class is influenced by internal and external factors, internal factors come from teaching and learning process, the school environment and the lack of teachingÂ softskills while external factors come from the lack of students acknowledgment and awareness of family and society values and the last but not least is the influence of the rapidly worldwide technology development.This study is conducted to investigate the case appears in teaching and learning speakingregarding to problems on implementing the politeness principle faced by students. Recently,phenomenon happen among students in conversation that fail to provide appropriate politenessespecially toward elders can be illustrated as the basic assumptions from the way they useutterances and their failure on paying attention of social class, age, sex when they communicate toothers. This phenomenon brings questions that become the bases of the aims of this study to find outproblem appears on implementing politeness principle in teaching and learning speaking, to findout factors cause the problems appear, and formulate suitable recommendations to provokestudents using appropriate utterances and maxim in order to make good relationships anddistinguish context toward different age, sex and status of conversation participants who theyinteract with. This study belongs to the case study research and the data collected fromobservations and interviews. The findings show that the problems often made by students are theyutter wrong expressions for certain situations, they do not greet, thank and ask for sorry to anyonethey involved with included the elders. The problems that faced by students in implementingpoliteness principal in speaking class is influenced by internal and external factors, internalfactors come from teaching and learning process, the school environment and the lack of teachingsoftskills while external factors come from the lack of students acknowledgment and awareness offamily and society values and the last but not least is the influence of the rapidly worldwidetechnology development.